2019
DOI: 10.1002/wer.1016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of carbon source and COD/N on the concurrent operation of partial denitrification and anammox

Abstract: In this study, concurrent operation of anammox and partial denitrification within a nonacclimated mixed culture system was proposed. The impact of carbon sources (acetate, glycerol, methanol, and ethanol) and COD/NO3 − -N ratio on partial denitrification selection under both short-and long-term operations were investigated. Results from short-term testing showed that all carbon sources supported partial denitrification. However, acetate and glycerol were preferred due to their display of efficient partial den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 45 publications
5
59
3
Order By: Relevance
“…93% PdN efficiency observed in the batch kinetic studies, 2. 80% PdN efficiency at the highest possible target, achieved in the mainstream pilot with acetate as COD source (Le et al, 2019a), 3. Lower ranges of PdN efficiency (60%, 50%, and 30%) which were based on results from pilot testing with fermentate.…”
Section: Operation Cost Savings For Pdna Using Fermentatementioning
confidence: 99%
“…93% PdN efficiency observed in the batch kinetic studies, 2. 80% PdN efficiency at the highest possible target, achieved in the mainstream pilot with acetate as COD source (Le et al, 2019a), 3. Lower ranges of PdN efficiency (60%, 50%, and 30%) which were based on results from pilot testing with fermentate.…”
Section: Operation Cost Savings For Pdna Using Fermentatementioning
confidence: 99%
“…While the AnAOB process is easily controlled whenever nitrite is available, PdN selection has become a critical step determining success of the PdN‐AnAOB approach (Kumar & Lin, ). Nitrite accumulation as indicator of PdN has been reported in many studies when fast carbon sources such as acetate (Du et al, ; Ge et al, ; Gong et al, ; Le et al, ; Van Rijn, Tal, & Barak, ; Yang, Wang, & Zhou, ) or glycerol (Baideme et al, ; Bill et al, ; Park, Brotto, Loosdrecht, & Chandran, ; Sharp et al, ; Uprety, ) were used for denitrification. Furthermore, other research also showed that COD/N ratio, pH, DO level, and SRT could be important factors impacting PdN performance (Almeida, Júlio, Reis, & Carrondo, ; Beccari, Passino, Ramadori, & Tandoi, ; Glass & Silverstein, ; Obaja, MacÉ, & Mata‐Alvarez, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous literatures have evidenced that simple micromolecule organic materials could easily harvest NO 2 --N accumulating organisms compared with complex carbon source. For instance, ethanol [26], methanol [23], acetate [27], even the biodegradable organics in urban sewage were exploited as denitrifiers electronic donors. However, easily biodegradable organics were rarely detected in current practical wastewater, i.e., municipal wastewater, sludge digestion solution and manufacturing wastewater.…”
Section: Carbon Sourcesmentioning
confidence: 99%
“…--N in raw wastewater, which was critical factor for terminating NO 3 --N reduction only to NO 2 --N. The ratio of COD/NO 3 --N largely determined the denitrification process and controlled the reduction rate of NO 3 --N [26]. Widely reported appropriate COD/NO 3 --N ratio for PD process ranged from 2.0~3.5, of which high NTR performance and anammox bacteria suitable influent substrate (NH 4 + -N/NO 2 --N=1.30) could be available [8,22,31].…”
Section: Cod/no 3 --N Limited Cod/no 3 --N Means Low Level Cod or Sufmentioning
confidence: 99%